New WS9326A Congeners from Streptomyces sp. 9078 Inhibiting Brugia malayi asparaginyl-tRNA Synthetase - Yu, Zhiguo (2012)
[Image: see text] Lymphatic filariasis is caused by the Brugia malayi parasite. Three new congeners of the depsipeptide WS9326A (1), WS9326C (2), WS9326D (3) and WS9326E (4), were isolated from Streptomyces sp. 9078 by using a B. malayi asparaginyl-tRNA synthetase (BmAsnRS) inhibition assay. WS9326D specifically inhibits the BmAsnRS, kills the adult B. malayi parasite, and does not exhibit significant general cytotoxicity to human hepatic cells, representing a new lead scaffold for antifilarial drug discovery.